Original paperInsulin resistance and selected metabolic, inflammatory and anthropometric parameters in the adult population of the Tarnawa Dolna municipality in the Bieszczady - Żyła, Zofia Grażyna (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2011)
Introduction: Raven noted an association between insulin resistance and cardiovascular consequences and type 2 diabetes mellitus 20 years ago. In 1985 Mathew prescribed the method of insulin resistance designation using the mathematic model HOMA-IR. Aim : To estimate insulin resistance HOMA-IR in the adult population of Tarnawa Dolna City in the Bieszczady Mountains according to gender, assess selected parameters in people with HOMA-IR  2.5 and HOMA-IR < 2.5, and determine dependence between HOMA-IR and the above parameters. Material and methods : Hundred and fifty-four adult people (101 women and 53 men), medium age 52.5 years, from Tarnawa City constituted the material. Blood pressure was examined. Blood samples were obtained for plasma glycaemia, lipidogram and serum insulinaemia and hsCRP. All people were measured and weighed, body mass index (BMI) was calculated, waist circumference was obtained, and HOMA-IR was calculated. The cut-off point 2.5 for HOMA-IR was accepted. Results: Insulin resistance as HOMA-IR designated in 24.7% of the examined population was observed without a difference between women and men. Significant differences between HOMA-IR  2.5 and < 2.5 were observed according to TG and waist circumference. In women all examined parameters were significantly different except HDL. In men BMI, waist circumference and HDL were significantly different in HOMA-IR  2.5 and HOMA-IR < 2.5. In the whole study group correlations between HOMA-IR and all parameters were noted. In the female group correlations concerned all examined parameters, in the male group HDL and waist circumference. Conclusions : Insulin resistance in 24.7% occurred in the whole study group without a significant difference between women and men. The HOMA-IR  2.5 group was statistically different from the HOMA-IR < 2.5 group according to selected parameters more strongly in women. Body mass was the main factor determining insulin resistance in the whole study group as well as in men and women. Streszczenie Wstęp : Ponad 20 lat temu Raven po raz pierwszy zauważył związek pomiędzy opornością insulinową a konsekwencjami sercowo-naczyniowymi i cukrzycą typu 2. W 1985 r. Mathew opisał metodę oznaczania insulinooporności za pomocą wzoru matematycznego HOMA IR. Cel: Ocena oporności insulinowej HOMA IR w populacji dorosłych mieszkańców gminy Tarnawa Dolna w zależności od płci, wybranych parametrów u osób z HOMA IR  2,5 i HOMA IR < 2,5 oraz określenie zależności pomiędzy HOMA IR a powyższymi parametrami. Materiał i metody : Grupę badawczą stanowiły 154 dorosłe osoby (101 kobiet i 53 mężczyzn) w średnim wieku 52,5 roku. Osobom tym mierzono ciśnienie tętnicze, pobierano krew do oznaczenia glikemii i lipidogramu w osoczu oraz insulinemii i hsCRP w surowicy. Badanych ważono i mierzono, obliczano wskaźnik masy ciała (body mass index – BMI) oraz mierzono obwód pasa. Ze wzoru wyliczano HOMA IR. Za punkt odcięcia dla HOMA IR przyjęto 2,5 µU/ml × mmol/l. Wyniki : Oporność insulinową określoną jako HOMA IR  2,5 zaobserwowano u 24,7% badanej populacji bez istotnej różnicy pomiędzy grupą kobiet i mężczyzn. Występowały istotne różnice pomiędzy grupą HOMA IR  2,5 i grupą HOMA IR < 2,5 odnośnie do triglicerydów i BMI. U kobiet wszystkie badane parametry różniły się istotnie, oprócz stężenia frakcji HDL cholesterolu. U mężczyzn BMI, obwód pasa i stężenie frakcji HDL różniły się istotnie w grupie HOMA IR  2,5 i HOMA IR < 2,5. W całej badanej grupie występowały korelacje między HOMA IR a wszystkimi badanymi parametrami. Wśród kobiet zależności dotyczyły wszystkich badanych parametrów, natomiast u mężczyzn stężenia frakcji HDL cholesterolu i obwodu pasa. Wnioski : Oporność insulinowa występowała u 25% badanej grupy, bez istotnej różnicy pomiędzy kobietami i mężczyznami. Grupa HOMA IR  2,5 różniła się istotnie od grupy HOMA IR < 2,5 pod względem wybranych parametrów, z większym nasileniem u kobiet. Masa ciała była głównym czynnikiem determinującym oporność insulinową w całej grupie badanej zarówno wśród kobiet, jak i mężczyzn.